2020
DOI: 10.1002/celc.202000278
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Active Oxygen Reduction Catalysts with Reduced Noble Metal Loadings through Potential Triggered Support Passivation

Abstract: The development of stable, cost‐efficient and active materials is one of the main challenges in catalysis. The utilization of platinum in the electroreduction of oxygen is a salient example where the development of new material combinations has led to a drastic increase in specific activity compared to bare platinum. These material classes comprise nanostructured thin films, platinum alloys, shape‐controlled nanostructures and core–shell architectures. Excessive platinum substitution, however, leads to structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…However, since the height of the Pt islands/clusters is controllable (up to the reaching of the 0.13 nm 84 ) they are of interest to catalytic applications in their own way. Concomitantly, ALD technique was found to be the more effective method to form continuous ultrathin Pt layers on graphene oxide 87 and titanium carbide (TiC) 88 , respectively. For example, the use of MeCpPtMe 3 as a Pt precursor and ozone as a co-reactant enabled the formation of stable Pt films with thicknesses ranging from 1 to 6 monolayers 88 .…”
Section: Osmiummentioning
confidence: 99%
See 3 more Smart Citations
“…However, since the height of the Pt islands/clusters is controllable (up to the reaching of the 0.13 nm 84 ) they are of interest to catalytic applications in their own way. Concomitantly, ALD technique was found to be the more effective method to form continuous ultrathin Pt layers on graphene oxide 87 and titanium carbide (TiC) 88 , respectively. For example, the use of MeCpPtMe 3 as a Pt precursor and ozone as a co-reactant enabled the formation of stable Pt films with thicknesses ranging from 1 to 6 monolayers 88 .…”
Section: Osmiummentioning
confidence: 99%
“…Concomitantly, ALD technique was found to be the more effective method to form continuous ultrathin Pt layers on graphene oxide 87 and titanium carbide (TiC) 88 , respectively. For example, the use of MeCpPtMe 3 as a Pt precursor and ozone as a co-reactant enabled the formation of stable Pt films with thicknesses ranging from 1 to 6 monolayers 88 .…”
Section: Osmiummentioning
confidence: 99%
See 2 more Smart Citations
“…36 This disproportionate dissolution indicated that the performance losses observed for CS NPs were all due to the dissolution of CS NP particles with imperfect Pt surface coverage, suggesting that the stability of Pt/TiWC catalysts could be improved with enhanced synthetic methods to achieve complete coverage of the labile TiWC cores. 36 In addition to achieving complete Pt coverage, the stability of CS NP catalysts could be optimized for ORR in future work through the incorporation of more stable core materials 101 or additional phases such as phosphides. 102…”
Section: Path Forward: An Emphasis On Electrochemical Stabilitymentioning
confidence: 99%